IMPLEMENTASI PERATURAN DESA TENTANG ANGGARAN PENDAPATAN BELANJA DESA (APBDes) DI DESA KUALA TERUSAN KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN TAHUN 2010 - Pratiwi, Dita; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this paper is to investigate the implementation of the Regulation on Budget Rural Village ( APBdes ) in the village of Kuala canal and explain the obstacles that prevent the implementation of village regulations on the implementation of the APBDes . Implementation of rural development programs through the village of financing by using the appropriate regulatory APBDes village where the village chief and his staff Kuala canal should invite the public to rural development programs, so that people know that the program will be conducted, but no socialization village chief and his staff to the community. It Regulations APBDes conducted village of Kuala Canal Village Chief District of Pangkalan Kerinci in accordance with Regulation No. 7 of 2010 the village has not been completely worked well, which is not the implementation of good communication between the head of the village with his staff and the community, especially in the delivery of information and invitations are usually performed by IHC or forum through Friday prayer meeting did not take place and also the low village of personnel resources. In the implementation, a village about APBDes in 2010 has not been the implementation of the disposition of the work and the tasks and responsibilities within the organization structure in the village of Kuala canal is still not fully implemented, it is due to the implementation in 2010, a village about APBDes ineffectiveness caused everything about the work and the implementation of entirely APBDes handled by the village head Kuala Canal. Keywords : Communication , Resources , Disposition , Bureaucratic Structure